Larvicidal activity of microparticles of Melissa officinalis L. essential oil (Lamiaceae) against Aedes aegypti (Diptera, Culicidae) (Research, Society and Development, 2021)
This study aimed to evaluate the larvicidal activity of essential oil microparticles (EO) of Melissa officinalis L. against Aedes aegypti. The leaves of M. officinalis were collected in the municipality of São José de Ribamar, Maranhão, Brazil, later dried, crushed and ground. 90g of the dried leaves were used to obtain the EO by the hydrodistillation method. For the synthesis of microencapsulated EO, 60g of sodium alginate (2.5% m/v) was added to the mixture of 15g of Tween 20 with 6g of EO. The mixture was homogenized and drips over CaCl2 5% m/v solution for the hardening of particles via crosslinking. The microparticles were washed with distilled water in filter and dried at 35ºC/24h and 15 days at tamb (30ºC). The eggs of Aedes aegypti were collected at the Federal University of Maranhão by the ovitrampas method. The larvae that hatched were fed until they reached the fourth instar. Groups of larvae (n=20) were submitted to solutions of EO and microparticles of 10-90 mg/L . After 24 h, live and dead larvae were counted and LC50 was calculated by the Reed&Muench method, using Cheng's criterion for classification of active potential. All larvae presented mortality in all concentrations tested. The LC50 obtained for the EO was 40.60 mg/L and for the microparticles 22.10 mg/L, both classified as active according to the adopted criterion, but it is observed that the microparticles increased the larvicidal potential of the EO. Through the results obtained, it is concluded that the microparticles formulated with the EO proved to be efficient in the face of the larvae of Aedes aegypti, being interesting and important in controlling and combating the mosquito that transmits dengue.